KAJIAN HUKUM PENYALAHGUNAAN KECERDASAN BUATAN DALAM KASUS DEEPFAKE DI INDONESIA - Desiana Monika Bulu; Fransiska Modhe Dua; Nadia Menu Ola; Sonya Wiwin Olifia Ay; Maria Yuliani Doe Rato; Fadil Mas'ud; Desiana Bulu (STKIP Subang, 2026)
The development of artificial intelligence (AI) technology has brought about significant changes in people's digital lives, including the emergence of deepfake technology that can manipulate images, sounds, and videos to appear authentic. Initially, this technology was used for the needs of the creative and entertainment industries, but over time, it has the potential to be misused to spread hoaxes, defamation, digital fraud, and even manipulate public opinion. This study aims to analyze the legal regulations related to the misuse of artificial intelligence technology, particularly deepfake technology, in Indonesia and to analyze the urgency of establishing specific regulations related to AI. The research method used is a normative juridical approach through literature study. Data were obtained from primary legal materials in the form of the Electronic Information and Transactions Law, the Personal Data Protection Law, the Criminal Code, and the Criminal Code, as well as secondary legal materials in the form of books, journals, and relevant scientific articles. The results of the study indicate that Indonesia does not yet have specific regulations that comprehensively regulate artificial intelligence and deepfakes. However, several provisions in the ITE Law, the Criminal Code, the PDP Law, and the Civil Code can be used as a legal basis for addressing the misuse of this technology. However, existing regulations still have limitations in providing legal certainty, personal data protection, or oversight mechanisms for AI use. Therefore, the development of comprehensive, adaptive, and binding AI-specific regulations is necessary to ensure legal certainty, protect public rights, and foster a safe and responsible digital ecosystem in Indonesia.